Звери: [в 2 томах] (Альфред Брем ; [комментарии.: Е. А. Коблик, С. В. Крускоп]) - Брем Альфред Эдмунд (Жизнь животных, 2000)
Экземпляры: (20170406) / Инвентарный номер: 2355 / Цена: / Авт.знак: Б 89 / ББК: 28.693.36